Active and Uncontrolled Asthma Among Children Exposed to Air Stack Emissions of Sulphur Dioxide from Petroleum Refineries in Montreal, Quebec: A Cross-Sectional Study - Leylâ Deger; Céline Plante; Louis Jacques; Sophie Goudreau; Stéphane Perron; John Hicks; Tom Kosatsky; Audrey Smargiassi (Canadian Respiratory Journal)
BACKGROUND: Little attention has been devoted to the effects on children’s respiratory health of exposure to sulphur dioxide (SO2) in ambient air from local industrial emissions. Most studies on the effects of SO2 have assessed its impact as part of the regional ambient air pollutant mix.